2021
DOI: 10.1016/j.plabm.2021.e00214
|View full text |Cite
|
Sign up to set email alerts
|

Determining procalcitonin at point-of-care; A method comparison study of four commercial PCT assays

Abstract: Objective Procalcitonin (PCT) testing adds value in the early detection of infection and sepsis, as well as in management of antibiotic therapy. We determined the analytical and diagnostic performance of four PCT assays at POC. Methods PCT assays on AQT90 FLEX, Getein 1100, mLabs, and Finecare POC analyzers, in whole blood and plasma, were analyzed for repeatability, linearity, accuracy and concordance, by comparing with our reference PCT assay on the Cobas E602 system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
3
9
1
Order By: Relevance
“…The LIP tool was developed based on the pathophysiological nature of sepsis-induced immunosuppression, procoagulant dysfunction, and the systemic inflammatory response, and the three biomarkers included in the LIP scoring system can be routinely assessed at most medical institutions worldwide. Many medical institutions can also carry out point-of-care testing (POCT), which greatly shortens the screening time for sepsis [19][20][21][22] . The combination of multiple biomarkers has complementary advantages, and ROC analysis showed that the LIP scoring tool has satisfactory screening efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The LIP tool was developed based on the pathophysiological nature of sepsis-induced immunosuppression, procoagulant dysfunction, and the systemic inflammatory response, and the three biomarkers included in the LIP scoring system can be routinely assessed at most medical institutions worldwide. Many medical institutions can also carry out point-of-care testing (POCT), which greatly shortens the screening time for sepsis [19][20][21][22] . The combination of multiple biomarkers has complementary advantages, and ROC analysis showed that the LIP scoring tool has satisfactory screening efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…There are other, less commonly used techniques, such as immunoturbidimetric assay. [ 57 ] [ 60 ] [ 61 ] [ 62 ] Ferritin IFA Immunoturbidimetric, LAA, ELISA, RIA, IRMA Among the POC devices is the ichroma II [ 57 ] [ 63 ] [ 64 ] Hematological Lymphocyte Automatic hematological analyzer Automatic hematological analyzer, flow cytometer and Coulter counting The NLR is calculated as the ratio of the absolute neutrophil count to the absolute lymphocyte count. Hematological analyzers such as the HemoCue WBC DIFF system are available for POC detection.…”
Section: Covid-19 Biomarkers: From Diagnosis To Prognosis and Predict...mentioning
confidence: 99%
“…Examples of POC analyzers available in 2021 for PCT testing include the AQT90 FLEX (Radiometer, Copenhagen, Denmark), mLabs (Micropoint, Shenzhen, China), Finecare (Wondfo, Guangzhou, China), and Getein 1100 (Getein Biotech Inc., Nanjing, China) [ 6 ]. Studies indicate that the AQT90 FLEX PCT assay demonstrates good agreement and precision compared to the reference immunoassay [ 6 ]. A coefficient of variation (CV) of less than 5% was observed in both plasma and whole blood at 0.5 ng/mL and 2.0 ng/mL PCT levels [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that the AQT90 FLEX PCT assay demonstrates good agreement and precision compared to the reference immunoassay [ 6 ]. A coefficient of variation (CV) of less than 5% was observed in both plasma and whole blood at 0.5 ng/mL and 2.0 ng/mL PCT levels [ 6 ]. However, the assay stability is only up to 8 months and requires conditions of 2–8 degrees for storage of the reagent [ 6 ].…”
Section: Introductionmentioning
confidence: 99%